Impacts of Covid-19 on the Tourist Perceived Risk: A Conceptual Approach - Ana GARCEZ; Ricardo Fontes CORREIA; Adriano COSTA (Communications of International Proceedings, 2021)
The Covid-19 pandemic generated an unprecedented global health outbreak and economic crisis. Therefore, and due to the growing attention given to its effects on the tourism sector and the numerous predictions made at micro and macro levels, this study seeks to understand the transformations in tourist consumer behavior caused by the covid-19 pandemic. Thus, based on several assumptions, an explanatory model was built that addresses both the demand side (new consumer preferences) and the supply side (measures and strategies to combat the impacts generated by the perceived risk acquired during the confinement period). The model developed reflects a permanent impact of the Covid-19 crises on the touristic consumer behavior, accelerating the migration to online, with a greater emphasis on safety, hygiene and health, as well as environmental and sustainability awareness.
Keywords: Tourism; COVID-19; Impacts; Motivations; Tourist Consumer; Perceived Risk